Applying trade-off curve to support set-based design application in an aerospace company - Mohsin, Esraa M.; Abdulateef, Osamah F.; Al-Ashaab, Ahmed (Institut Agama Islam Negeri, 2020)
Companies compete greatly with each other today, so they need to focus on innovation to develop their products and make them competitive. Lean product development is the ideal way to develop product, foster innovation, maximize value, and reduce time. Set-Based Concurrent Engineering (SBCE) is an approved lean product improvement mechanism that builds on the creation of a number of alternative designs at the subsystem level. These designs are simultaneously improved and tested, and the weaker choices are removed gradually until the optimum solution is reached finally. SBCE implementations have been extensively performed in the automotive industry and there are a few case studies in the aerospace industry. This research describe the use of trade-off curve as a lean tool to support SBCE process model in CONGA project, using NASA simulation software version 1.7c and CONGA demonstration program (DEMO program) to help designers and engineers to extract the design solution where it exists according to the customer requirement and to extract alternative nearest solutions from the previous project that meet customer requirement to achieve low noise engine at an aerospace company and also extract the infeasible region where the designers cannot make any prototype in this region before manufacturing process begin, that will lead to reducing rework, time and cost.
Keywords: Knowledge management; Lean product development; SBCE; Trade-off curve